The hydroclimatology of Gorgona Island: seasonal and ENSO-related Patternsa - Blanco, Juan F. (Actualidades Biológicas, 2012)
Most small watersheds in the Tropical Eastern Pacific remain ungauged, and discharge analyses using gauge and simulated data have been published only for a few large rivers. I analyzed a 20-yr record of rainfall and stream discharge from Gorgona Island, a natural national park located 30 km offshore in the Pacific Ocean of Colombia to explore intra- and inter-annual patterns and drivers. Gorgona Island receives > 6.600 mm of annual rainfall thus feeding numerous permanent streams. Inter Tropical Convergence Zone-driven seasonal rainfall patterns (unimodal) were consistent regardless of interannual variability. However, a large yearly variation was observed between May and August. Monthly and annual rainfall in Gorgona Island was greater than at a neighboring continental-coastal area, suggesting the occurrence of orographic and convective rain. El Niño Southern Oscillation slightly influenced interannual variation in rainfall, but it strongly influenced stream discharge. The importance of the Chocó Jet Current and Meso-Scale Stationary Systems is discussed